Legislation on the offence of rape in Icelandic criminal law - Ragnheiður Bragadóttir (Bergen journal of criminal law & criminal justice, 2020)
In recent years the concept of rape has been frequently discussed in Iceland. The chapter on sexual offences in the Icelandic General Penal Code (GPC) was revised in its entirety in 1992 and 2007, and important amendments were made on the provision on rape, section 194 of the GPC. The amendments in 2007 included a new, broad definition of the concept of rape, which was intended to cover all incidents where sexual intercourse or other sexual relations were performed against the victim’s will. In 2018 amendments were made on section 194 on rape, where the word “consent” was included in the provision. This does not constitute a substantive change since lack of consent was already an underlying element of the provision due to the amendments in 2007. The article addresses the academic discussion and societal views that were the precursor of these amendments, evaluates the current provision and discusses whether further amendments are needed.